MSU-IIT faculty administrators' potential to be job burnout - Farid, Muhammad; Orejana, Annie J. (2001)
This study was designed to determine empirically whether certain working conditions and personality traits are significantly associated with the potential to be job burnout. The results will eventually be used as a basis for policy formulation to address job burnout among the faculty administrators in MSU-Iligan Institute of Technology. It also sought to verify the null hypothesis about the absence of significant relationship between the prescribed demographic personal profile and the potential to get job burnout. The findings of the study will hopefully give valuable information on the potential to be job burnout among faculty administrators. Hence, it could be prevented through some policies and programs. The results of the statistical tests show that the potential to be job burnout is significantly associated with the working conditions in terms of extra workload and time pressure and with the personality traits in terms of being pessimistic, delicate, sympathetic, and idealistic. In the demographic personal profile variables, only the family size criterion is significantly correlated with the potential to be job burnout. Moreover, stepwise regression analysis shows that working conditions such as extra workload, time pressure, and routine work, together with the personality traits in terms of being pessimistic, delicate/sensitive, dedicated, and sympathetic are the predictors of the potential to be job burnout. Using the Pearson Correlation Coefficient, the result showed that only family size has a significant relationship with the potential to be job burnout in terms of depersonalization and emotional exhaustion. This implies that they could show a negative behavior with their peers, students and other people at work. This is manifested by their being callous and tired toward people at work and tend to be withdrawn. Family size could contribute to their tendency to be burned out due to the difficulty and stress in managing family problems. Although the average family size of the respondents is only 3 and some of their children may not be living with them, there is greater emotional exhaustion due to their separation. Moreover, with an extended family system, the state of tiredness, frustration, boredom and depression consequently result to emotional exhaustion leading to job burnout. The potential to be job burnout has a significant relationship with the working condition in terms of extra workload. The faculty administrators aside from their administrative work are also given extra assignments as chair or members of various committees and are also carrying overload units, research work, extension service and are active in many civic/community organizations. Under these circumstances, stress and over-fatigue result in decreased efficiency, frequent mistakes and sickness. This phenomenon eventually results to be job burnout. The study reveals that time pressure exhibits a significant relationship with the proneness to be job burnout in terms of feeling of low personal accomplishment and depersonalization. This indicates that the faculty administrators faced with meeting deadlines as administrator and faculty will feel that he has not done his best because of the little time he has for all the tasks he has to accomplish and he has no time to communicate with his other colleagues and friends. The finding shows that there is a significant relationship between the potential to be job burnout with being pessimistic, delicate/ sensitive, sympathetic and idealistic. Pessimistic persons are easily discouraged, worry a lot and have skepticism on their ability which consequently create for themselves pressure and stress. They develop negative physiological feeling of over-fatigue and tiredness and tend to be demotivated to socialize. Hence, they easily succumb to job burnout.
Keywords: Job burnout; Mindanao studies